Implications of silver nanoparticles for H. pylori infection: modulation of CagA function and signaling - Hochvaldova, Lucie; Posselt, Gernot; Wessler, Silja; Kvítek, Libor; Panáček, Aleš (Frontiers in Cellular and Infection Microbiology, 2024)
Background Helicobacter pylori infection poses a significant health burden worldwide, and its virulence factor CagA plays a pivotal role in its pathogenesis. Methods In this study, the interaction between H. pylori-infected AGS cells and silver nanoparticles (AgNPs) was investigated, with a focus on the modulation of CagA-mediated responses, investigated by western blotting. Both, the dose-dependent efficacy against H. pylori (growth curves, CFU assay) and the impact of the nanoparticles on AGS cells (MTT assay) were elucidated. Results AGS cells infected with H. pylori displayed dramatic morphological changes, characterized by elongation and a migratory phenotype, attributed to CagA activity. Preincubation of H. pylori with AgNPs affected these morphological changes in a concentration-dependent manner, suggesting a correlation between AgNPs concentration and CagA function. Conclusion Our study highlights the nuanced interplay between host-pathogen interactions and the therapeutic potential of AgNPs in combating H. pylori infection and offers valuable insights into the multifaceted dynamics of CagA mediated responses.